2010
DOI: 10.1002/anie.200906931
|View full text |Cite
|
Sign up to set email alerts
|

η3‐Vinylborane Complexes of Platinum and Nickel: Borataallyl‐ and Alkyl/Borataalkene‐Like Coordination Modes

Abstract: Anyone for pi? The vinylborane PhHCCH‐B(C6F5)2 reacts with zero‐valent Group 10 transition‐metal precursors to form η3‐vinylborane complexes. The platinum tri‐tert‐butylphosphine complex exhibits an η3‐borataallyl‐like coordination mode whereas the nickel bis(triphenylphosphine) complex tends towards alkyl/borataalkene coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…M -Z interactions embedded in multi-center systems (such as those involved in the coordination of B-H bonds, 11 of B-CQC [12][13][14][15] or B-CRC 16 moieties, etc.) After a general presentation of the nature and characteristics of M -Z interactions, the various types of known complexes featuring such M -Z interactions, unsupported or supported by donor buttresses, are presented.…”
Section: Introductionmentioning
confidence: 99%
“…M -Z interactions embedded in multi-center systems (such as those involved in the coordination of B-H bonds, 11 of B-CQC [12][13][14][15] or B-CRC 16 moieties, etc.) After a general presentation of the nature and characteristics of M -Z interactions, the various types of known complexes featuring such M -Z interactions, unsupported or supported by donor buttresses, are presented.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the PtÀC a and PtÀC b distances in 6 A (2.184(5) and 2.194(5) , respectively) are shorter than those in 1 by 0.041 and 0.135 . Even shorter PtÀC distances have previously been described for [Pt(PtBu 3 )(VB Ph )] [VB Ph = (E)-PhHC=C(H)-B(C 6 F 5 ) 2 ; two independent molecules in the unit cell; PtÀC a = 2.126(4)/2.130(4) ; PtÀC b = 2.137(4)/2.155(4) ; PtÀB = 2.273(5)/2.319(5) ], [41] likely due to decreased steric hindrance and the greater Lewis acidity of the borane in VB Ph (VB Ph was shown to be an overall acceptor ligand in [Pt(PtBu 3 )-(VB Ph )]). The BÀC a distance in 6 A is 1.546(8) , compared with 1.551(5) in 1 and 1.517(6)/1.519 (7) in [Pt(PtBu 3 )(VB Ph )], but unfortunately, the standard deviation associated with the BÀC a bond in 6 A is too large to draw any conclusions regarding the extent of multiple bond character.…”
Section: Introductionmentioning
confidence: 99%
“…Such distortions are typical of late transition metal-allyl complexes, [42] suggesting that the vinylborane in 6 A is more borataallyl-like than alkyl/borataalkene-like. [41] Complex 6 A isomerises over a period of six days at room temperature to an approximate 45:55 mixture of the original isomer and a new isomer, 6 B, giving rise to a new set of 31 P (55.7 and 23.3 ppm), 11 B (30 ppm) and 195 Pt (À4840 ppm) signals. As with 6 A, isomer 6 B features an h 3 BCC-coordinated (Z)-(BÀCPh=CHPh) group: 1) 1 H-13 C HSQC NMR confirmed that the vinyl proton is located in the b-position, 2) coupling between the BÀCPh=CHPh signal and the o-BPh signal in a selective 1D 1 H-1 H ROESY NMR experiment demonstrated that the ligand has a Z-arrangement of the phenyl substituents on the vinyl group (the vinyl CH proton in 6 A shows an analogous ROESY coupling), 3) the 11 B NMR chemical shift (30 ppm) confirmed coordination of boron to platinum, and 4) vinyl group 1 H-195 Pt, 13 C- 195 Pt and 13 C- 31 the regiochemistry of the BCC unit preserved (Scheme 3; isomer 6 B shows through-space coupling between the BÀCPh=CHPh group and the PCMe 3 group).…”
Section: Introductionmentioning
confidence: 99%
“…Scheme3.Various h 3 -BCC-coordinatedc omplexes: I: h 3 -coordinated boranebridged diylide; [33] II, III,and IV: h 3 -BCC-coordinatedt riarylboranes; [23,34,35] V: borataalkene; [36] VI:borataallyl. [36] Chem.E ur.J.2015, 21,13732 -13738 www.chemeurj.org ReÀCb ond. The same effect is also manifested in the CÀOd istances.…”
Section: Reactivity Of Rhodaboratrane 1with Metal Carbonyl Compoundsmentioning
confidence: 99%